How does monetary policy affect aggregate demand? A multimodel approach for Hungary - Zoltán M. Jakab; Viktor Várpalotai; Balázs Vonnák (Magyar Nemzeti Bank, 2006)
This paper assesses the effect of monetary policy on major components of aggregate demand. We use three different macromodels, all estimated on Hungarian data of the past 10 years. All three models indicated that after an unexpected monetary policy tightening investments decrease quickly. The response of consumption is more ambiguous, but it is most likely to increase for several years, which may be explained by the slow adjustment of nominal wages. On the other hand, we could not detect any significant change in net exports during the first couple of years after the shock. The weak response of net exports can be due to the fact that the drop in exports is coupled with a fall in imports of almost the same magnitude, highlighting the relative importance of the income-absorption effect, as opposed to the expenditure-switching effect.
Keywords: E20; E27; E52; 330; monetary transmission mechanism; macromodels; VAR; impulse responses; Geldpolitische Transmission; Makroökonomik; VAR-Modell; Ungarn